The ACTTION Guide to Clinical Trials of Pain Treatments, part II: mitigating bias, maximizing value - Dworkin, Robert H. (Pain Rep, 2021)
Summaries of the articles included in part II of the ACTTION Guide to Clinical Trials of Pain Treatments are followed by brief overviews of methodologic considerations involving precision pain medicine, pragmatic clinical trials, real world evidence, and patient engagement in clinical trials.